THE GOVERNMENT OF THE RUSSIAN EMPIRE NATIONAL IN TURKESTAN LIMITATION OF EDUCATION AND ITS NEGATIVE CONSEQUENCES - Nodira Ibragimovna Alimova (Journals Park Publishing, 2023)
The present work was done on the basis of the national Archives of Uzbekista and demonstrates that there was a great attention to the development of national educational policy since long time. After invading Turkistan by Russia the policy was focused on reducing the national people’s education and limiting quantity of Madrassas and schools. As a result of reducing their numbers the number of mudarrises, domullas and mullas had been decreased, and consequently damaged the upbringing of young generation, as it was reported.
Keywords: Scientific education, madrassa, old school, new model school, colonial administration.